2015
DOI: 10.1111/1467-9566.12373
|View full text |Cite
|
Sign up to set email alerts
|

Violence in general practice: a gendered risk?

Abstract: This article focuses on the extent to which violence against family doctors in England is experienced in gendered terms. It draws on data from two studies: a postal survey of 1,300 general practitioners (GPs) (62% response rate) and in‐depth interviews with 26 doctors who have been assaulted or threatened; and 13 focus groups with primary care teams and 19 in‐depth interviews with GPs who had expressed an interest in the topic of violence against doctors. Most GPs, regardless of gender, reported receiving verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…Fear and embarrassment are well-established inhibitors of engagement with patients; embarrassment gets in the way of clinicians investigating sensitive topics (Tomlinson, 1998) or undertaking intimate examinations (Hine & Smith, 2014), while fear of aggressive patients impedes the patient-provider relationship (Elston & Gabe, 2016). In the view taken in the current work, the elicitation of avoidance-promoting emotions is central to problematic clinical engagement.…”
Section: Statement Of Contributionmentioning
confidence: 89%
See 1 more Smart Citation
“…Fear and embarrassment are well-established inhibitors of engagement with patients; embarrassment gets in the way of clinicians investigating sensitive topics (Tomlinson, 1998) or undertaking intimate examinations (Hine & Smith, 2014), while fear of aggressive patients impedes the patient-provider relationship (Elston & Gabe, 2016). In the view taken in the current work, the elicitation of avoidance-promoting emotions is central to problematic clinical engagement.…”
Section: Statement Of Contributionmentioning
confidence: 89%
“…In the view taken in the current work, the elicitation of avoidance-promoting emotions is central to problematic clinical engagement. Fear and embarrassment are well-established inhibitors of engagement with patients; embarrassment gets in the way of clinicians investigating sensitive topics (Tomlinson, 1998) or undertaking intimate examinations (Hine & Smith, 2014), while fear of aggressive patients impedes the patient-provider relationship (Elston & Gabe, 2016). However, considerably less is known about how disgust might impact clinical interactions.…”
Section: Statement Of Contributionmentioning
confidence: 99%
“…Demographic changes in the physician population should also be considered. As the percentage of female physicians increases, preventive measures should focus on female physicians to reverse the trend of increasing patient-physician aggression 17 23. Because one third of the male physicians experienced aggression too, they might also benefit from preventive actions.…”
Section: Discussionmentioning
confidence: 99%
“…The 12-month prevalence of aggression towards general practitioners (GPs) was 54.9% for verbal aggression and 23.4% for physical aggression 1. In a survey in the UK 78% of all GPs experienced at least one verbal incident in the previous 2 years 2. A recent cross-sectional study among Flemish GPs showed that only about 5% never encountered aggression.…”
Section: Introductionmentioning
confidence: 99%